A light-assisted rechargeable zinc-air battery and a method for preparing the same

By using FeCu-ZIF composite material as the photoelectrode in the photo-assisted zinc air battery, the problem of single function and low activity of the photocatalyst in the prior art is solved, and more efficient photoelectric conversion and cell life are achieved.

CN115133181BActive Publication Date: 2025-02-28LIAONING UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210894553.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-28
Publication Date
2025-02-28
Estimated Expiration
2042-07-28

AI Technical Summary

Technical Problem

The existing photocatalysts of photo-assisted zinc air batteries have single function and low activity, resulting in low photoelectric conversion efficiency, and a high charging potential will lead to catalyst corrosion and affect service life.

Method used

FeCu-ZIF composite material is used as the photoelectrode, and by loading FeCu-ZIF powder on the foam nickel, a photoelectrode with dual active center and good stability is formed to reduce the corrosion effect during the charging process.

Benefits of technology

It improves photocatalytic activity, reduces charging voltage, extends the service life of the electrode, and significantly improves the energy efficiency of zinc air batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention provides a light-assisted rechargeable zinc-air battery and a preparation method thereof, belonging to the technical field of metal-air batteries. The technical scheme adopted is: dissolving 2-methylimidazole in anhydrous methanol for ultrasound; placing copper sheet, Zn(NO3)2·6H2O and Fe(NO3)3·9H2O in anhydrous methanol for ultrasound; mixing the above two solutions, centrifuging, washing and drying to obtain FeCu-ZIF powder; dropping N-methylpyrrolidone into a mixture of FeCu-ZIF powder, carbon black and polyvinylidene fluoride, grinding into a paste solid, applying the paste solid on nickel foam, calcining, cooling to room temperature to obtain FeCu-ZIF photoelectrode; assembling the FeCu-ZIF photoelectrode and zinc electrode using a zinc-air battery device, i.e., obtaining a light-assisted rechargeable zinc-air battery. The battery of the present invention uses a FeCu-ZIF photoelectrode with a porous structure, a bimetallic active center and good conductivity on the surface, realizing the synergistic conversion of solar energy, electrical energy and chemical energy in one device, with low economic cost and high energy utilization efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal-air batteries, and in particular relates to a light-assisted rechargeable zinc-air battery and a preparation method thereof. Background Art

[0002] The main energy storage technologies on the market include fuel cells, metal-air batteries and water electrolysis. In this regard, metal-air batteries have the advantages of both traditional batteries and fuel cells, because they have a higher theoretical specific energy density (usually higher than 1000Wh kg -1 ), low cost and environmental friendliness have become the key research objects in energy storage technology.

[0003] In recent years, a zinc-air battery has entered people's field of vision. Compared with traditional lithium-air batteries, the theoretical specific energy of zinc-air batteries (ZAB) is as high as 1086Wh kg -1 , about five times that of lithium-air batteries. Zinc is more stable than lithium in nature, does not react violently with water and air, and has a higher safety factor. In addition, zinc-air batteries also have the advantages of low redox potential, flat discharge voltage, long service life and environmental friendliness. So far, hearing aids, radars, and navigation lights equipped with zinc-air batteries have been widely used in daily life.

[0004] Light-assisted zinc-air batteries can convert light energy into chemical energy and store it in the battery. This battery not only has the advantages of traditional zinc-air batteries, but also uses new semiconductor materials to replace the precious metal substances in traditional zinc-air batteries, significantly reducing costs. The charging process of light-assisted zinc-air batteries is as follows: when illuminated, the photoelectrode absorbs sunlight to generate photogenerated electron-hole pairs. The photogenerated holes have strong oxidation ability and are transferred to the surface of the photocatalyst to participate in the OER reaction, oxidizing OH- to generate O2. The generated electrons move from the external circuit to the zinc electrode to convert Zn(OH)4 2- The discharge process is just the opposite. The photogenerated electrons participate in the ORR reaction, and the photogenerated holes migrate to the surface of the zinc electrode to oxidize Zn to Zn 2+ .

[0005] Light-assisted zinc-air batteries can meet the needs of large-scale energy storage in the future market. However, most photocatalysts have the disadvantages of single function and low activity, which leads to low photoelectric conversion efficiency. In addition, the high charging potential will cause catalyst corrosion and thus affect the service life of the catalyst. Therefore, the FeCu-ZIF composite material prepared by the present invention not only has dual active centers, but also has good stability. Loading it on nickel foam can effectively reduce the corrosion effect during charging. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a light-assisted rechargeable zinc-air battery and a preparation method thereof.

[0007] The technical solution adopted by the present invention is:

[0008] A light-assisted rechargeable zinc-air battery, the preparation method of which comprises the following steps:

[0009] 1) Synthesis of FeCu-ZIF powder: 2-methylimidazole was dissolved in anhydrous methanol and ultrasonicated for 10 min; copper sheet, Zn(NO3)2`·6H2O and Fe(NO3)3·9H2O were placed in anhydrous methanol and ultrasonicated for 1 h; the two solutions were mixed and stirred at room temperature for 4 h; the mixed solution was centrifuged, washed and dried to obtain FeCu-ZIF powder;

[0010] 2) Preparation of FeCu-ZIF photoelectrode: The FeCu-ZIF powder obtained in step 1) is uniformly mixed with carbon black and polyvinylidene fluoride, and N-methylpyrrolidone is added dropwise thereto after sufficient grinding, and the mixture is further ground into a paste solid, and then the paste solid is smeared on nickel foam, and calcined in a muffle furnace. After the calcination is completed, the mixture is taken out and cooled to room temperature to obtain a FeCu-ZIF photoelectrode;

[0011] 3) Assembly of a light-assisted rechargeable zinc-air battery: The FeCu-ZIF photoelectrode obtained in step 2) is used as the working electrode and the zinc sheet is used as the counter electrode, and zinc-air battery devices are used for assembly to obtain a light-assisted rechargeable zinc-air battery.

[0012] Furthermore, in the above-mentioned light-assisted rechargeable zinc-air battery, the synthesis method of the FeCu-ZIF powder includes the following steps: dissolving 5262 mg of 2-methylimidazole in 120 mL of anhydrous methanol, and ultrasonicating for 10 minutes to completely dissolve it; cutting two 2 cm × 2 cm copper sheets, placing them in a hydrochloric acid solution for ultrasonicating for 15 minutes to remove surface oily substances and oxides, and then rinsing the copper sheets with deionized water and methanol three times each, dissolving 1814 mg of Zn(NO3)2`·6H2O and 532 mg of Fe(NO3)3·9H2O in 120 mL of anhydrous methanol, and then placing the two treated copper sheets in the solution for ultrasonic treatment for 1 hour; mixing the above two solutions and stirring at room temperature for 4 hours; centrifuging the mixed solution, washing, and drying at room temperature to obtain FeCu-ZIF powder.

[0013] Furthermore, in the above-mentioned light-assisted rechargeable zinc-air battery, the hydrochloric acid solution has a volume ratio of concentrated hydrochloric acid: water = 1:3.

[0014] Furthermore, in the above-mentioned light-assisted rechargeable zinc-air battery, the centrifugal speed is 10000r / min and the centrifugal time is 10min.

[0015] Furthermore, in the above-mentioned light-assisted rechargeable zinc-air battery, the preparation method of the FeCu-ZIF photoelectrode includes the following steps: taking 200 mg of FeCu-ZIF powder, mixing it evenly with carbon black and polyvinylidene fluoride, grinding it thoroughly, adding N-methylpyrrolidone dropwise thereto, continuing to grind it into a paste solid, then smearing the paste solid on nickel foam, putting it into a muffle furnace for calcining, and taking it out after the calcination is completed and cooling it to room temperature to obtain a FeCu-ZIF photoelectrode.

[0016] Furthermore, in the above-mentioned light-assisted rechargeable zinc-air battery, the mass ratio of the FeCu-ZIF powder to the carbon black and polyvinylidene fluoride is 8:1:1.

[0017] Furthermore, in the above-mentioned light-assisted rechargeable zinc-air battery, the volume of each drop of N-methylpyrrolidone is 0.1 mL, and it is dropped 6 times in total.

[0018] Furthermore, in the above-mentioned light-assisted rechargeable zinc-air battery, the mass of the paste solid applied on each piece of nickel foam is 80-100 mg.

[0019] Furthermore, in the above-mentioned light-assisted rechargeable zinc-air battery, the calcination temperature is 450° C. and the calcination time is 2 hours.

[0020] Furthermore, the above-mentioned light-assisted rechargeable zinc-air battery, the assembly method of the light-assisted rechargeable zinc-air battery is as follows: using FeCu-ZIF photoelectrode as the working electrode, the zinc sheet as the counter electrode, using a partition to separate the FeCu-ZIF photoelectrode and the zinc sheet so that the two do not contact each other, and at the same time ensuring that both are in the same electrolyte; the front of the light-assisted rechargeable zinc-air battery device is a quartz glass plate, so that sunlight can irradiate the photoelectrode of the battery; using glass glue to seal the quartz glass and the light-assisted rechargeable zinc-air battery device.

[0021] The beneficial effects of the present invention are:

[0022] 1. The present invention is to 2+ and Cu 2+A ZIF-derived carbon skeleton with iron and copper coordination was synthesized by doping in ZIF-8, and it was loaded on nickel foam by coating and calcination to prepare FeCu-ZIF photoelectrode materials with excellent photocatalytic activity and stability, and assembled into light-assisted zinc-air batteries. The battery can convert solar energy into chemical energy while charging, and further convert chemical energy into electrical energy during subsequent discharge. This method is a new way to utilize solar energy. The battery was placed in the dark and simulated sunlight environment for long-term charge and discharge performance tests. The results showed that under light conditions, the battery charging voltage was about 1.8V, which was 0.2V lower than that under dark conditions; the discharge voltage was about 1.0V, which was 0.2V higher than that under dark conditions. The data proved that the ZIF-derived carbon skeleton with iron and copper coordination can absorb sunlight to a certain extent, reduce the charging voltage, effectively reduce the degradation of the electrode, and enhance the service life of the zinc-air battery. In addition, the material can exist stably in the electrolyte and has more active sites, which improves the battery efficiency while ensuring the safety performance of the battery.

[0023] 2. The present invention designs and synthesizes FeCu-ZIF materials by using a calcination method. The material has the characteristics of bimetallic active centers, a porous surface structure, and a large specific surface area. It can accelerate the separation and transfer of photogenerated electron-hole pairs and has high photocatalytic activity.

[0024] 3. The present invention prepares a FeCu-ZIF dual-functional photoelectrode material, which significantly increases the charging potential under light conditions while reducing the discharge potential of the battery.

[0025] 4. The present invention utilizes semiconductor materials to replace precious metal electrodes, utilizes solar energy to compensate for the charging voltage of zinc-air batteries, and realizes the coordinated conversion of solar energy and chemical energy into electrical energy.

[0026] 5. The significant advantage of the present invention is that by using FeCu-ZIF photoelectrodes in the battery, solar energy, electrical energy and chemical energy can be converted into each other in one device, which improves energy utilization efficiency while simplifying the system configuration and realizes green development. In addition, the photocatalyst has abundant raw materials, is easy to prepare, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a scanning electron microscope image of the FeCu-ZIF photoelectrode.

[0028] Figure 2 This is a partial magnified scanning electron microscope image of the FeCu-ZIF photoelectrode.

[0029] Figure 3 It is a schematic structural diagram of the light-assisted rechargeable zinc-air battery of the present invention.

[0030] Figure 4 This is a long-term charge and discharge performance test diagram of the light-assisted rechargeable zinc-air battery of the present invention.

[0031] Figure 5 It is a physical picture of the present invention based on the light-assisted rechargeable zinc-air battery lighting up the LED small bulb, wherein A is a physical picture of the light-assisted rechargeable zinc-air battery not lighting up the LED small bulb under dark conditions, and B is a physical picture of the light-assisted rechargeable zinc-air battery lighting up the LED small bulb under simulated sunlight. DETAILED DESCRIPTION

[0032] In order to better understand the present invention, the present invention is further described below through examples. It should be understood that the purpose of the following implementation is to better explain the content of the present invention, rather than to impose any limitation on the protection scope of the present invention.

[0033] Example 1 Preparation of a light-assisted rechargeable zinc-air battery

[0034] (I) Preparation of FeCu-ZIF photoelectrode

[0035] 1) Synthesis of FeCu-ZIF powder:

[0036] Weigh 5262 mg of 2-methylimidazole and dissolve it in 120 mL of anhydrous methanol, and ultrasonicate it for 10 minutes to completely dissolve it; cut two 2 cm × 2 cm copper sheets, place them in a hydrochloric acid solution (prepared with a volume ratio of concentrated hydrochloric acid: water = 1:3) and ultrasonicate them for 15 minutes to remove surface oily substances and oxides, then rinse the copper sheets three times with deionized water and methanol respectively, weigh 1814 mg of Zn(NO3)2·6H2O and 532 mg of Fe(NO3)3·9H2O and dissolve them in 120 mL of anhydrous methanol, and then put the two treated copper sheets into the solution for ultrasonic treatment for 1 hour; mix the above two solutions, stir them at room temperature for 4 hours, put them into a centrifuge and centrifuge them at a speed of 10000 r / min for 10 minutes, after the end, ultrasonically clean the solid obtained by centrifugation with methanol, and put them into the centrifuge again at a speed of 10000 r / min for 10 minutes, and dry the solid obtained by centrifugation at room temperature to obtain FeCu-ZIF powder.

[0037] 2) Preparation of FeCu-ZIF photoelectrode:

[0038] Weigh 200 mg of the FeCu-ZIF powder prepared in step 1), mix it evenly with carbon black and polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, put it in a mortar and grind it thoroughly, then add N-methylpyrrolidone dropwise, 0.1 mL each time, for a total of 6 times, continue to grind it into a paste-like solid, then apply 100 mg of the paste-like solid on each piece of nickel foam, put it in a muffle furnace and calcine it at 450°C for 2 h. After the calcination is completed, take it out and cool it to room temperature to obtain the FeCu-ZIF photoelectrode.

[0039] (II) Testing

[0040] The morphology and thickness of FeCu-ZIF photoelectrode were characterized by SEM images, such as Figure 1 and Figure 2 As shown, FeCu-ZIF has a truncated rhombic dodecahedron morphology. 2+ and Cu 2+ The introduction of Fe leads to morphological changes and significant increase in crystal size, which is due to the partial deprotonation of 2-methylimidazole linker and the formation of Fe 2+ and Cu 2+ Wider growth direction in the presence of.

[0041] (III) A light-assisted rechargeable zinc-air battery

[0042] like Figure 3 As shown in the figure, a structure of a light-assisted rechargeable zinc-air battery is as follows: a FeCu-ZIF photoelectrode is used as a working electrode, a zinc sheet is used as a counter electrode (negative electrode), a partition is used to separate the FeCu-ZIF photoelectrode from the zinc sheet so that the two do not contact each other and both are ensured to be in the same electrolyte; the front of the light-assisted rechargeable zinc-air battery device is a quartz glass plate so that sunlight can irradiate the photoelectrode of the battery; glass glue is used to seal the quartz glass and the light-assisted rechargeable zinc-air battery device to prevent electrolyte leakage; the electrolyte is a mixed solution of 1M potassium hydroxide-0.02M zinc acetate dihydrate, and when irradiated, the electrolyte is simulated sunlight (a 500W xenon lamp is used as a light source, an AM 1.5 filter, and an incident light intensity of 100mW / cm 2 )

[0043] 1) Long-term charge and discharge performance test

[0044] like Figure 4As shown in the figure, the zinc-air battery using FeCu-ZIF photoelectrode as the working electrode has a charging voltage of about 2.0V and a discharge voltage of about 0.8V under dark conditions during the 2h test. The corresponding charge-discharge voltage gap is large, about 1.2V, and the energy efficiency is also low. Under simulated sunlight, the charging voltage is about 1.8V, which is 0.2V lower than that under dark conditions; the discharge voltage is about 1.0V, which is 0.2V higher than that under dark conditions. From this, we can see that the electrode has photocatalytic activity, which improves the energy efficiency of the battery.

[0045] 2) Practical application of light-assisted rechargeable zinc-air batteries to light up LED bulbs under simulated sunlight

[0046] like Figure 5 As shown, under simulated sunlight, two light-assisted rechargeable zinc-air batteries can light up the LED bulb when connected in series.

Claims

1. A light-assisted rechargeable zinc-air battery, characterized in that: The preparation method comprises the following steps: 1) Synthesis of FeCu-ZIF powder: 5262 mg of 2-methylimidazole was dissolved in 120 mL of anhydrous methanol and ultrasonicated for 10 min to completely dissolve it; two 2 cm×2 cm copper sheets were cut and placed in a hydrochloric acid solution for ultrasonication for 15 min to remove surface oily substances and oxides, and then the copper sheets were rinsed three times with deionized water and methanol respectively; 1814 mg of Zn(NO3)2·6H2O and 532 mg of Fe(NO3)3·9H2O were dissolved in 120 mL of anhydrous methanol, and then the two treated copper sheets were placed in the solution for ultrasonication for 1 h; the above two solutions were mixed and stirred at room temperature for 4 h; the mixed solution was centrifuged, washed, and dried at room temperature to obtain FeCu-ZIF powder; 2) Preparation of FeCu-ZIF photoelectrode: 200 mg of FeCu-ZIF powder obtained in step 1) was mixed evenly with carbon black and polyvinylidene fluoride, and N-methylpyrrolidone was added dropwise thereto after sufficient grinding, and the mixture was further ground into a paste solid, and then the paste solid was smeared on nickel foam and calcined in a muffle furnace. After the calcination was completed, the mixture was taken out and cooled to room temperature to obtain a FeCu-ZIF photoelectrode; 3) Assembly of a light-assisted rechargeable zinc-air battery: The FeCu-ZIF photoelectrode obtained in step 2) is used as the working electrode and the zinc sheet is used as the counter electrode, and zinc-air battery devices are assembled to obtain a light-assisted rechargeable zinc-air battery.

2. A light-assisted rechargeable zinc-air battery according to claim 1, characterized in that: The hydrochloric acid solution has a volume ratio of concentrated hydrochloric acid: water = 1:

3.

3. A light-assisted rechargeable zinc-air battery according to claim 1, characterized in that: The centrifugal speed is 10000 r / min, and the centrifugal time is 10 min.

4. A light-assisted rechargeable zinc-air battery according to claim 1, characterized in that: The mass ratio of the FeCu-ZIF powder to carbon black and polyvinylidene fluoride is 8:1:

1.

5. A light-assisted rechargeable zinc-air battery according to claim 1, characterized in that: The volume of the N-methylpyrrolidone added each time was 0.1 mL, and the addition was performed 6 times in total.

6. A light-assisted rechargeable zinc-air battery according to claim 1, characterized in that: The paste-like solid is applied on each piece of nickel foam in an amount of 80-100 mg.

7. A light-assisted rechargeable zinc-air battery according to claim 1, characterized in that: The calcination temperature is 450° C. and the calcination time is 2 h.

8. A light-assisted rechargeable zinc-air battery according to claim 1, characterized in that: The assembly method of the light-assisted rechargeable zinc-air battery is as follows: using a FeCu-ZIF photoelectrode as a working electrode and a zinc sheet as a counter electrode, using a partition to separate the FeCu-ZIF photoelectrode from the zinc sheet so that the two do not contact each other and at the same time ensuring that the two are in the same electrolyte; the front of the light-assisted rechargeable zinc-air battery device is a quartz glass plate so that sunlight can irradiate the photoelectrode of the battery; and using glass glue to seal the quartz glass and the light-assisted rechargeable zinc-air battery device.

Citation Information

Patent Citations

  • Metal-air battery based on silver-copper catalysis and preparation method thereof

    CN104538709A

  • Rechargeable zinc air battery based on sunlight promotion strategy and preparation method thereof

    CN112864497A